NEUROMUSCULAR AND JOINT DYSFUNCTION OF THE TEMPOROMANDIBULAR JOINT - Yu. N. MAYBORODA; O. Yu. KHOREV (Кубанский научный медицинский вестник)
Aim. To analyse the modern concepts of neuromuscular and joint dysfunction. The article presents the current notion of parafunctional violations of masticatory muscles associated with the loss of teeth, anomalies and deformations in the dento-facial system. We touched the issues of functional overload of periodontium on the background of muscle hypertrophy and related infringement of proprioceptive impulses, which are based on the change of coordination, rhythmic of chewing movements and kinetics of the temporomandibular joint.